2023
DOI: 10.1108/jtf-09-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing university students in conducting ecotourism

Abstract: PurposeThis study examines the factors that influence the ecotourist behavior of university students. The understanding of what motivates these students can inform future suggestions for strategies and actions in ecotourism.Design/methodology/approachThe study was applied to university students of the University of Medellín, Colombia. It was an exploratory empirical study that surveyed a total of 696 students.FindingsThe results show that students with a positive attitude toward ecology tend to be interested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Sanchez's research highlights the role of ecological attitude in shaping individuals' interest in nature-related activities and their inclination towards ecotourism. The study suggests a positive correlation between a positive ecological attitude, engagement in ecological experiences during leisure, and a higher likelihood of participating in ecotourism (Sánchez-Torres et al, 2023).…”
Section: Intention For Ecotourismmentioning
confidence: 77%
See 1 more Smart Citation
“…Sanchez's research highlights the role of ecological attitude in shaping individuals' interest in nature-related activities and their inclination towards ecotourism. The study suggests a positive correlation between a positive ecological attitude, engagement in ecological experiences during leisure, and a higher likelihood of participating in ecotourism (Sánchez-Torres et al, 2023).…”
Section: Intention For Ecotourismmentioning
confidence: 77%
“…Building on the concept of ecotourist identity (Sánchez-Torres et al, 2023), it proposed that individuals who strongly identify themselves as ecotourists, embracing the associated environmental values and behaviors, will be more inclined to express the intention to engage in ecotourism. This hypothesis aligns with the idea that a well-defined ecotourist identity fosters a commitment to ecotourism activities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Usually, students like to travel, visit various destinations and consume numerous hospitality and tourism products and services, particularly in a foreign land (Sánchez-Torres et al ., 2023). Their experience with this amalgam of products and services forms and shapes their visit experience, influencing their future visit intention (Sánchez-Torres et al ., 2023).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Usually, students like to travel, visit various destinations and consume numerous hospitality and tourism products and services, particularly in a foreign land (Sánchez-Torres et al ., 2023). Their experience with this amalgam of products and services forms and shapes their visit experience, influencing their future visit intention (Sánchez-Torres et al ., 2023). Many scholars have suggested that the student tourist segment is lucrative (Bai et al ., 2004; Kim et al ., 2007), representing 22% of global market segments (Patwary and Rashid, 2016).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Studying low-carbon tourism and spatial effects could help to improve the local ecological environment and achieve the sustainable development of the tourism economy [8]. The improvement in ecotourism efficiency could enhance the utilization efficiency of ecotourism resources [9], reduce conflicts among local residents, and encourage tourism departments to consider the local tourist-carrying capacity and strengthen the planning of ecological tourism resources, which can be used to achieve sustainable tourism development [10].…”
Section: Introductionmentioning
confidence: 99%